2011
DOI: 10.1111/j.1365-294x.2011.05045.x
|View full text |Cite
|
Sign up to set email alerts
|

Scanning the genome for gene SNPs related to climate adaptation and estimating selection at the molecular level in boreal black spruce

Abstract: Outlier detection methods were used to scan the genome of the boreal conifer black spruce (Picea mariana [Mill.] B.S.P.) for gene single-nucleotide polymorphisms (SNPs) potentially involved in adaptations to temperature and precipitation variations. The scan involved 583 SNPs from 313 genes potentially playing adaptive roles. Differentiation estimates among population groups defined following variation in temperature and precipitation were moderately high for adaptive quantitative characters such as the timing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
147
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(175 citation statements)
references
References 90 publications
23
147
1
1
Order By: Relevance
“…In similar comparisons made between Picea mariana and P. glauca (divergence time >10 MYA), Prunier, Laroche, Beaulieu, and Bousquet (2011) found more adaptive similarities at the gene family level (paralogs) than at the gene level (orthologs). The redundancy of functions among recently duplicated genes in conifers could have offered the possibility for selection to act on paralogous genes in different species (Namroud et al., 2010).…”
Section: Discussionmentioning
confidence: 79%
“…In similar comparisons made between Picea mariana and P. glauca (divergence time >10 MYA), Prunier, Laroche, Beaulieu, and Bousquet (2011) found more adaptive similarities at the gene family level (paralogs) than at the gene level (orthologs). The redundancy of functions among recently duplicated genes in conifers could have offered the possibility for selection to act on paralogous genes in different species (Namroud et al., 2010).…”
Section: Discussionmentioning
confidence: 79%
“…Eckert et al (2010) identified 22 candidate loci (BF log 10 42.0) associated with climate variables from 1730 loci in 682 loblolly pine tree samples covering the full range of the species. Prunier et al (2011) also identified 10 candidate loci above 99% confidence interval in black spruce. The proportion of detected loci (1.3% and 1.7%, respectively) associated to the climate variables was very similar with our results.…”
Section: Detection Of Outlier Locimentioning
confidence: 99%
“…Genome scanning is an effective and useful method for detecting genetic differentiation and candidate genes associated with specific phenotypes or environmental variables in forest tree species (Eveno et al, 2008;Namroud et al, 2008;Eckert et al, 2010;Holliday et al, 2010;Neale and Kremer, 2011;Prunier et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This trend indicates that larger sets of genes should be analyzed in conifers to get a more complete picture of LD of the gene space. The information obtained should contribute to build more efficient gene SNP arrays for use in association studies (González-Martínez et al, 2008) and for outlier detection among natural populations or environments (Namroud et al, 2008;Prunier et al, 2011). Accordingly, we sequenced a large number of genes in natural populations of white spruce to assess LD and its contributing factors more completely, and to compare with results obtained for other conifers.…”
Section: Introductionmentioning
confidence: 99%